LOTS OF THINGS TO KNOW ABOUT WEATHER - Bone, Emily; Gaigalova, Katia; Webb, Katie; Knott, Lizzie; Trend, Roger, Dr. (London : Usborne Publishing Limited, 2023)
"A collection of amazing facts exploring the wonders of weather. Ever wondered how fast the fastest winds blow? How heavy is a cloud? Where are the driest and wettest places on Earth? Find out the answers and learn lots more curious and original facts about the weather in this delightful information book"--Publisher's description
Includes index
6-10 years old.
Keywords: Weather -- Juvenile literature; Climatology -- Juvenile literature; Juvenile works